Kondisi Hidro-Oseanografi di Wilayah Perairan Desa Peropa , Kabupaten Wakatobi, Sulawesi Tenggara - Al Firman Firman; La Ode Muh. Gunawan Giu (Jurnal Rekayasa Geofisika Indonesia, 2024)
The waters of Peropaare part of the water area in South Kaledupa District, Wakatobi Regency, Southeast Sulawesi. This research is needed to determine the components of hydro-oceanography, namely tides, bathymetry, currents and waves. Tidal conditions were obtained through analysis using the Admiralty Method from tidal data for 15 days, resulting in a semidiurnal mixed tide prevalling type with the highest tide of 3.16 m and the lowest low tide of -0.29 m. The bathymetry measurement method uses hydroacoustic principles via a single beam echosounder instrument, obtaining a depth of 10 m closest to the coastline at a distance of 70 m in the northwest part of the research area and at a distance of 20 m in the southeastern part of the research area. Conditions for the movement of ocean currents and waves are carried out using a hydrodynamic model approach. Based on the results of the ocean current model, the direction of the current tends to follow the coastline with the dominant flow direction moving east and north at high tide and south and west at low tide, with a current speed range of 0.075-0.13 m/s at the highest tide and 0.04 -0.1 m/s at lowest ebb. The wave heights that occur in the research area range from less than 0.75 m to 2.5 m.